Flexing Phenomenon in Tiktok: A Critical Review in the Perspective of Sharia Economic Law - Latifatul Ma'rifah; Dwi Noviatul Zahra (Saqifah: Jurnal Hukum Ekonomi Syariah, 2025)
The phenomenon of flexing or showing off wealth through social media, especially TikTok, has become a trend among millennials and Gen Z. It takes various forms, from displaying expensive skincare, fantastic sales achievements, to luxurious lifestyles packaged as marketing content. It takes various forms, ranging from displaying expensive skincare, fantastic sales achievements, to luxurious lifestyles packaged as marketing content. Despite the surface economic impact, this practice raises ethical and normative issues from the perspective of Sharia Economic Law. This research aims to critically examine the phenomenon of flexing through a normative approach with the theory of Maqashid Sharia, Islamic consumption ethics, and the rules of dar'ul mafasid muqaddamun 'ala jalbil mashalih. The method used is descriptive qualitative with a library research approach, accompanied by social data and case studies from TikTok actors such as Shella Saukia and Daviena Skincare. The results of the study show that the practice of flexing which is manipulative, riya, and image-oriented is contrary to the principles of hifz al-mal, hifz al-nafs, hifz al-'irdh, and even hifz al-din. Apart from causing social pressure and potential debt, flexing also disrupts the balance of maslahat values and fosters a consumptive culture. Therefore, it is important to encourage digital education based on sharia values and build ethical and moral awareness in social media so that the digital economy remains in line with the Islamic principles of justice, blessings, and social responsibility.